11C-L-methionine for evaluation of pancreatic exocrine function. Issue 11 (November 1981) - Syrota, A; Dop-Ngassa, M; Cerf, M; Paraf, A
Abstract : Pancreatic uptake of a natural amino acid, L-methionine, was measured in 58 patients using a scintillation camera. This was possible by labelling L-methionine with 11C, a short-lived isotope produced in a cyclotron. Time-activity-curves obtained in areas of interest selected over the pancreas in 25 normal subjects and in 14 alcoholic patients showed a plateau or a slight increase of activity with time. In contrast, in 19 patients with chronic pancreatitis an initial increase in radioactivity was followed by a decrease for 10 to 20 minutes and then by a plateau. The ratio of the height of the plateau at the 50th minute to the height of the peak was 0.74 +/- 0.21 in these patients, whereas it was 0.96 +/- 0.09 in the other subjects (P less than 0.001). This result was compared with direct measurements of 11C radioactivity and of amylase and bicarbonate in duodenal aspirate. The median amount of 11C incorporated into protein at the 70th minute was 53% of total activity in the control group, 28% in alcoholic patients, and only 3% in chronic pancreatitis, the differences between these values were highly significant. The absence of a peak of radioactivity in the duodenal juice, and the existence of a correlation between total 11C output and amylase output suggested that there was no release of protein in the duodenum in chronic pancreatitis. These results also suggested that the peak observed by external detection could be due to amino acid back-diffusion from the pancreas into the blood. External detection with 11C-L-methionine could be used for the assessment of pancreatic dysfunction in man.